Parents' experiences of their child's assessment on an epilepsy surgery pathway: A qualitative study. (October 2021) - Nelson, Fiona; Gray, Victoria; Woolfall, Kerry
Highlights: Consideration for paediatric epilepsy surgery is complex and time consuming, yet there is lack of research exploring how this process might impact on families. Interviews with parents highlight that initial discussions about the possibility of surgery were unexpected and shocking, but also a source of hope. Unclear or inconsistent communication and lack of information about the steps, assessments and timeframes involved in the surgery assessment process led to some parents feeling 'out of control, ' uncertain, and in some cases distressed. Families would benefit from advance warning that surgery will be discussed at their next appointment, improved access to psychosocial and clinical psychological support during the long assessment process as well as a step-by-step guide of what will be involved with realistic timelines. Abstract: Purpose: Children's epilepsy surgery services (CESS) in the UK aim to improve outcomes for young children by increasing access to surgery. Consideration for surgery is complex and time consuming, yet there is lack of research exploring how this process might impact on families. This study aimed to explore parents' experiences of their child consideration for epilepsy surgery to inform future service development and delivery. Methods: Semi-structured interviews with parents of children (aged < six years) considered for surgery within the previous three years. Recruitment was through social media and purposive sampling of medical records. Data were analysed using a thematic and iterative approach. Results: 15 parents of 14 children were interviewed (13 mothers and 2 fathers). Initial discussions of epilepsy surgery were described as 'shocking' but also as a source of hope. However, unclear communication between staff and parents, including lack of information about the steps, assessments/investigations and timeframes involved in the process of assessment for surgery led to some feeling 'out of control, ' uncertain and in some cases distressed. Parents described examples of positive support from staff, yet many felt they needed additional general and emotional support throughout the epilepsy surgery pathway. Conclusions: Findings highlight the importance of providing clear and consistent information about the epilepsy surgery assessment to minimise parental distress and help facilitate a sense of control. Recommendations include providing parents with advance warning that surgery will be discussed at their next appointment, improved access to psychosocial and clinical psychological support and a step-by-step guide of the process with realistic timelines.